One-Pot Synthesis of Disperse Dyes Under Microwave Irradiation: Dyebath Reuse in Dyeing of Polyester Fabrics - Huda M. Mahmoud (Molecules, 2012)
A series of 4-hydroxyphenylazopyrazolopyrimidine disperse dyes were prepared via one-pot reactions of p-hydroxyphenylhydrazone, hydrazine hydrate, and acetylacetone or enaminones using microwave irradiation as an energy source. Structural assignments of the dyes were confirmed by X-ray crystallographic structure determination. Instead of discharging the dyebath after each dyeing cycle, the residual dyebath was spectrophotometrically analyzed and then pH readjusted for a repeat dyeing with longer time. Fastness of the dyed samples was measured after each recycle. Most of the dyed fabrics tested displayed good light fastness and excellent fastness to washing and perspiration. Finally, the biological activity of the synthesized dyes against Gram positive bacteria, Gram negative bacteria and yeast were evaluated.